Locally probing adatoms on graphene using perturbed angular correlation spectroscopy - Fenta, Abel Eduardo Silva (2020)
The interest in understanding the interaction between graphene and atoms and molecules that are adsorbed on its surface (adatoms and admolecules) spans a wide range of research ﬁelds and applications, for example, to controllably change the properties of graphene in electronic devices or to detect those changes in graphene-based sensors. Since the properties of graphene+adsorbent systems are strongly dependent on the adsorption conﬁguration (e.g. isolated versus clusters, their geometry and coordination), it is important to not only understand these eﬀects from a theoretical point of view, but also to be able to probe them experimentally. This thesis focuses on the interaction between graphene and adatoms (model cases: Hg, Cd, In and Ag) and admolecules (model case: HgO2), in terms of structural and electronic properties. The theoretical part of the research was based on density functional theory (DFT) calculations for diﬀerent heavy elements adsorbed on graphene (Hg, Ag, Cd and In). The binding energy and the electronic structure were calculated for various high-symmetry atomic conﬁgurations, from isolated adatoms to a continuous monolayer. Detailed studies were carried out for Hg-graphene, as a model system, i.e. testing various functionals and covering a wide range of nominal concentration. For Ag, Cd, In, we carried out more targeted studies, based on the extensive calculations for Hg. It was demonstrate that the binding energy depends on adatom concentration and as well on adsorption site (H, T, or B). All studied elements are predicted to be more stable as isolated adatoms than as a continuous monolayer. For each element, we calculated the electric ﬁeld gradient (EFG) parameters (Vzz and asymmetry parameter η). The EFG exhibits some variation when comparing diﬀerent high-symmetry sites, and also depends on the nominal concentration of the adatom relative to C atoms. Furthermore, the EFG is found to be sensitive to the local atomic structure, distinguishing isolated from monolayer conﬁgurations, and for some cases, varying signiﬁcantly with small variations in adatom position (at the sub-Å scale). Based on these calculations, we propose that the electric ﬁeld gradient, which can be measured using hyperﬁne techniques, can be used as an experimental observable providing insight on the local atomic conﬁguration and bonding stability of adatoms and admolecules on graphene. In particular, our calculations indicate that the level of detail that can be addressed via the EFG parameters (e.g. positional precision) increases with the stability (binding energy). In other words, the more stable the graphene-adatom system (i.e. more relevant in a application scenario), the more it lends itself to be studied using hyperﬁne techniques. Finally, adsorption of Hg on graphene in ambient conditions was experimentally studied using perturbed angular correlation (PAC) spectroscopy and 199mHg as probe nuclei. The combination of PAC measurements and DFT calculations allowed us to conclude that the majority of the Hg probes were adsorbed in the form of linear HgO2 molecules, which are adsorbed with higher binding energies (exceeding 1 eV) than isolated Hg adatoms (below 0.2 meV), i.e. oxygen plays a crucial role in stabilizing Hg adsorption on graphene. This work constitutes a proof-of-principle for the use of hyperﬁne techniques to study the interaction between graphene and adsorbed atoms and molecules, at the atomic scale. We also reported the ﬁrst PAC experiment based on the decay of 68mCu (6−,721 keV,3.75 min) and demonstrated the feasibility of using this Cu isotope as a probe nuclei for PAC for applications in the ﬁelds of solid state physics in particular in the context of graphene research. Since Cu is the most widely employed catalyst for obtaining graphene monolayers with reasonable quality, establishing 68mCu as a suitable PAC probe enables the use to study the inﬂuence of the Cu substrate, e.g. on grain size and orientation, number of layers and quality of the grown graphene. Our ﬁndings open the way for a wide range of applications of hyperﬁne techniques, including other 2-dimensional materials and other types of adatoms and phenomena. For example, the magnetic properties of transition elements can also be addressed, via the magnetic hyperﬁne interaction. In addition to the ability to probe multiple adatom properties and phenomena (e.g. structural and magnetic), such an experimental approach based on hyperﬁne techniques is generally compatible with applied electric or magnetic ﬁelds (often used to investigate basic and functional properties), ultra-high vacuum (typically necessary when studying surfaces, to minimize contamination), and low temperature operation (typically necessary when studying isolated adatoms, due to their high surface mobility).